Why University Students are addicted to Short Video TikTok?: A Malaysian Case - Nor Azilah Husin; Muhamad Saiful Hanif Khairi; Nurul Syazana Mohamad Nazeri; Eka Mariyanti (Sociometry Journal of Social Science, Art and Humanity, 2022)
The young generation nowadays loves to take pictures or make short videos to post on social media. This short video 15-second application has gained so much popularity that in 2019 almost one billion downloads in 150 markets worldwide and has 75 languages! Why is it so popular? Thus, this research is to study the factors that short video TikTok application addiction. The respondents were university students from both public and private Malaysian universities. We run descriptive statistics, correlation, and multiple regression to determine the relevance and significance of the relationship between the selected variables. This study proved that social factors, family factors, and lifestyle factors have significantly related to the short video TikTok addiction. The test revealed that a variance of 63.4% (R²) of Short Video TikTok addiction could be explained by social, family, and lifestyle factors. Social factors play the leading role in this addiction. The study implicated that this app could be a major influencer to the young generation.